A study on the evolutionary game theory of third-party governance of environmental pollution based on the quasi-co-owned relationship of pollution rights - Hu, Zikun; Wang, Yina; Liao, Wenjun; Tao, Tingyu; Zhang, Hao (Frontiers in Environmental Science, 2024)
The third-party governance of environmental pollution and the pollution rights trading system are two typical examples of modern environmental governance systems. In China, the quasi-co-owned relationship of pollution rights between pollution-discharging and pollution-control enterprises is the link through which to achieve synergy between the two factors. To explore how to achieve such synergy, first, the "principle of no-fault liability" is introduced, and the responsibilities of pollution-discharging enterprises and pollution-control enterprises are defined. Second, based on the quasi-co-owned relationship of pollution rights, a revenue-sharing mechanism for pollution rights trading is designed. Finally, a tripartite evolutionary game model consisting of pollution-discharging enterprises, pollution-control enterprises and local governments is constructed, and numerical simulation is performed. The results are as follows. (1) By setting a reasonable market trading price for pollution rights, a reward and punishment distribution coefficient, an improvement in reputation gains, and a saving in pollution rights indicators become conducive to the formation of cooperative relationships between pollution-discharging and pollution-control enterprises, for which the reasonable range of the reward and punishment distribution coefficient is (0.3, 0.4]. (2) Regardless of whether a government subsidy is provided, the optimal range of the revenue-sharing coefficient from pollution rights trading is [0.5,0.6]. (3) When a government subsidy is withdrawn, increasing the market trading price and surplus indicators of pollution rights can promote the stable operation of the third-party governance model. (4) An increase in policy support and administrative accountability of higher levels of government and a reduction in supervision costs for local governments can help these parties effectively avoid addressing the absence of local government supervision. It is recommended that third-party governance enterprises participate in pollution rights trading to implement the main responsibilities of pollution-discharging and pollution-control enterprises and to set a reasonable revenue-sharing coefficient and reward and punishment distribution coefficient of pollution rights.